Computer Network Reliability Optimization Calculation Based on Genetic Algorithm - Jiangtao Yu Jiangtao Yu (Universitas Ahmad Dahlan, 2013)
How to effectively reduce the network node link cost by improving the reliability of computer network transmission system is one of the important targets of computer network reliability optimization calculation. Therefore, in the computer network reliability optimization calculation, it is necessary to integrate the computer network link medium cost, network reliability optimization mathematical model and other factors. This paper describes genetic algorithm and its implementation process, as well as the application of genetic algorithm to the network link cost and network reliability optimization calculation. In addition, it is indicated from the simulation results that genetic algorithm can effectively solve the reliability optimization calculation problem which is difficult to solve by the traditional algorithm of network, so as to speed up the calculation speed of computer network and optimize the network calculation result.